2010
DOI: 10.1007/s00221-010-2206-6
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive transcranial magnetic stimulation (rTMS) of the dorsolateral prefrontal cortex (DLPFC) during capsaicin-induced pain: modulatory effects on motor cortex excitability

Abstract: Evidence by functional imaging studies suggests the role of left DLPFC in the inhibitory control of nociceptive transmission system. Pain exerts an inhibitory modulation on motor cortex, reducing MEP amplitude, while the effect of pain on motor intracortical excitability has not been studied so far. In the present study, we explored in healthy subjects the effect of capsaicin-induced pain and the modulatory influences of left DLPFC stimulation on motor corticospinal and intracortical excitability. Capsaicin wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
121
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(137 citation statements)
references
References 41 publications
12
121
3
1
Order By: Relevance
“…If recovery of DLPFC thickness and/or function is necessary for pain relief, then the DLPFC may be a target for treatment. In fact, it has already shown some promise in studies of short-and longterm analgesia from repetitive transcranial magnetic stimulation (rTMS) of the prefrontal cortex (Reid and Pridmore, 2001;Brighina et al, 2004;Graff-Guerrero et al, 2005;Avery et al, 2007;Borckardt et al, 2007Borckardt et al, , 2008Nahmias et al, 2009;Fierro et al, 2010). Interestingly, similar to treating depression with rTMS (Brunelin et al, 2007), these rTMS studies in pain seem to show a preferential effect for left-sided stimulation, the side that changed in the present study.…”
Section: Future Directionssupporting
confidence: 53%
See 1 more Smart Citation
“…If recovery of DLPFC thickness and/or function is necessary for pain relief, then the DLPFC may be a target for treatment. In fact, it has already shown some promise in studies of short-and longterm analgesia from repetitive transcranial magnetic stimulation (rTMS) of the prefrontal cortex (Reid and Pridmore, 2001;Brighina et al, 2004;Graff-Guerrero et al, 2005;Avery et al, 2007;Borckardt et al, 2007Borckardt et al, , 2008Nahmias et al, 2009;Fierro et al, 2010). Interestingly, similar to treating depression with rTMS (Brunelin et al, 2007), these rTMS studies in pain seem to show a preferential effect for left-sided stimulation, the side that changed in the present study.…”
Section: Future Directionssupporting
confidence: 53%
“…Several studies have also indicated abnormal cortical function in people with CLBP (Giesecke et al, 2004;Baliki et al, 2008;Lloyd et al, 2008;Kobayashi et al, 2009;Tagliazucchi et al, 2010). Evidence from pain neuroimaging and transcranial magnetic stimulation studies has linked the DLPFC to pain modulation (Lorenz et al, 2003;Brighina et al, 2004;Fierro et al, 2010), placebo analgesia (Wager et al, 2004;Krummenacher et al, 2010), perceived control of pain (Pariente et al, 2005;Wiech et al, 2006), and pain catastrophizing (Seminowicz and Davis, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…More anxious females might display lower pain thresholds, resulting in enhanced HPA-system reactivity (Stones et al, 1999). However, it has been shown that HF-rTMS applied to the left DLPFC results in reduced pain perceptions in healthy subjects (Borckardt et al, 2007;Fierro et al, 2010). In addition, the possibility that 'more anxious' healthy subjects are more susceptible to pain sensations, resulting in a more sensitive HPA system reactivity due to the real HFrTMS application, remains an open question as contrasting findings on the relationship between anxiety, stress and pain perception have been reported (Bement et al, in press).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the reduced rsFC from both MHb and LHb to the aMCC and pACC may link chronic pain states to changes in negative affect, pain, and cognitive control (Vogt 2005;Geha et al 2008;Shackman et al 2011). Another interesting finding relates to the reduced rsFC to the pgACC previously implicated in pain inhibition systems (Petrovic et al 2002;Wager et al 2004;Bingel et al 2006) and to the dlPFC repeatedly associated with pain modulation (Lorenz et al 2003;Brighina et al 2004;Fierro et al 2010), perceived control over pain (Pariente et al 2005;Wiech et al 2006), and pain catastrophizing (Seminowicz and Davis 2006).…”
Section: Hb Rsfc Group Differencesmentioning
confidence: 99%